Theoretical Determination of some Thermodynamic Properties of Selected Binary Liquid Alloys (2013)
Binary liquid alloys have found wide applications in electronics, communications, automotive and aerospace technologies. The development of new alloys and improvement of existing ones require accurate knowledge of thermodynamic variables of the constituent systems which may not be obtainable experimentally. Hence, there is always the need for theoretical investigation to complement experiment. This study was aimed at theoretical determination of the thermodynamic properties of nine binary liquid alloys. Nine liquid alloys (Al-Zn, Bi-In, Ga-Zn, Ga-Mg, Al-Ga, Sb-Sn, In-Pb, Ga-Tl and Al-Si) with insufficient theoretical investigation were selected for investigation using three different models. Quasi-lattice theory which connects thermodynamic and dynamical properties was employed to determine the concentration concentration fluctuation in the long-wavelength limit [Scc(0)], chemical short range order parameter (α1), free energy of mixing (GM), the concentration dependence of diffusion and viscosity of Al-Zn and Bi-In liquid alloys. Quasi-chemical approximation model for strongly interacting systems was used to investigate ordering and glass formation tendencies in Ga-Zn, Ga-Mg and Al-Ga binary alloys. A statistical thermodynamic theory was used to determine the mixing properties of Sb-Sn, In-Pb, Ga-Tl and Al-Si liquid alloys. The choice of model was influenced by the type of available experimental data. The Scc(0) and α1 showed that a reasonable degree of chemical order existed in Bi-In system, while Al-Zn liquid alloys exhibited a liquid miscibility gap or phase separation at all concentrations. The values of free energy of mixing at the equiatomic composition were -0.4986RT and -0.9344RT for Al-Zn and Bi-In alloys respectively. The free energy of mixing of Ga-Zn, Al-Ga and Ga-Mg alloys are almost symmetrical around the equiatomic composition with Ga-Mg being the most interacting, while Al-Ga is more interacting than Ga-Zn alloy. Apart from Ga-Mg alloys with negative enthalpy of mixing, both the enthalpy of mixing and entropy of mixing of the three Ga-based systems are positive and symmetrical about the equiatomic composition. In the concentration range 0 ≤ cAl ≤ 0.3 and 0.7 ≤ cAl ≤ 1, Al-Ga systems exhibited a glass-forming potential. The free energy of mixing, enthalpy of mixing and entropy of mixing of Sb-Sn and Al-Si liquid alloys exhibited negative deviations from ideality and were symmetric around the equiatomic composition, while In-Pb and Ga-Tl systems exhibited positive deviations with Ga-Tl alloys showing asymmetry behaviour. The compound formation in liquid phase was weaker in Al-Zn than in Bi-In alloys. The Sb-Sn and Al-Si liquid alloys had tendency for heterocoordination, while In-Pb and Ga-Tl exhibited homocoodination. The Ga-Zn and Al-Ga alloys exhibited homocoordination, whereas Ga-Mg alloys had tendency towards heterocoodination.